PERANCANGAN VIDEO PROMOSI PERUMAHAN TEGAL SARI INDAH PT. ANNISA MANDIRI MANDAU - Yopi Kurniawan; hendra afriwan (Universitas Negeri Padang, 2020)
Tegal Sari Indah Housing was established on July 25, 2018 which is located at Perinstis 2, Tegal Sari, Duri, this housing is one of the subsidized housing units that provide type 36 housing units. The lack of promotion by Tegal Sari Indah housing owners makes this housing not well known to the community, especially the Duri community. So the author makes the design of audio-visual media, in the form of video, this video has a duration of 3 minutes, which will be uploaded on youtube, with the design of this promotion it is expected that Tegal Sari Indah housing is known and able to compete with its competitors.Keywords: Video, promotion, Tegal Sari Indah Housing.